Elevated Thrombomodulin Plasma Levels as a Result of Endothelial Involvement in Plasmodium falciparum Malaria - Hemmer, Christoph J; Bierhaus, A; Riedesel, J v; Gabat, S; Liliensiek, B; Pitronik, P; Lin, J; Grauer, A; Amiral, J; Ziegler, R; Schieffer, S; Kern, P; Seitz, R; Egbring, R; Dietrich, M; Nawroth, P P (Thrombosis and Haemostasis, 1994)
We used thrombomodulin (TM) to assess the participation of the vascular endothelium in human Plasmodium falciparum (P. F.) malaria. Before therapy TM plasma levels were elevated in P. F. malaria and fell to normal values during therapy. Parasitemia, TNFα, elastase and TAT levels correlated directly with TM. Elevated TM levels can not be explained by increased synthesis, since incubating HUVEC with pretherapy serum of patients with P. F. malaria, but not reconvalescence serum, suppressed TM transcription. This was partially prevented by adding a TNFα neutralizing antibody to patient serum before incubation with HUVEC. However, TNFα does not release TM from cultured HUVEC in vitro. Coincubation of HUVEC with pretherapy serum together with neutrophils resulted in endothelial cell destruction, which could be partly prevented by a TNFα neutralizing antibody. Hence the increase of TM during P. F. malaria might reflect the concerted action of cytokines and neutrophils on HUVEC.